The Labor Market Effects of Mexican Repatriations: Longitudinal Evidence from the 1930s - Jongkwan Lee; Giovanni Peri; Vasil Yasenov (Institute of Labor Economics (IZA), 2019)
We examine the labor market consequences of an extensive campaign repatriating around 400,000 Mexicans in 1929-34. To identify a causal effect, we instrument county level repatriations with the existence of a railway line to Mexico interacted with the size of the Mexican communities in 1910. Using individual linked data we find that Mexican repatriations reduced employment of native incumbent workers and resulted in their occupational downgrading. However, using a repeated cross section of county level data, we find attenuated and non-significant employment effects and amplified wage downgrading. We show that this is due to selective in- and out-migration of natives.
Keywords: J15; J21; J61; N32; 330; Mexican repatriations; Great Depression; employment; immigration; railway